A comparative study of cardiac autonomic function tests in hypothyroid patients and euthyroid subjects - Paul, Rajesh Kumar; Pandey, Subodh; Chittawar, Sachin; Shrivastav, Kirtika (National journal of physiology, pharmacy and pharmacology, 2021)
MATERIALS AND METHODS This case-control study was carried out in the Department of Physiology in collaboration with the Department of Medicine and Department of Biochemistry, Gandhi Medical College and associate Hamidia Hospital, Bhopal, after approved by the ethical committee of the institution approval no. 3809-11/ MC/IEC/2018. Exclusion Criteria The following patients were excluded from the study. * Diabetes, hypertension, multiple sclerosis, and any other demyelinating disease which may lead to neuropathy * Patient with prior history of head injury, cerebrovascular accident, and epilepsy * The patient suffering from cardiovascular illness or cardiac autonomic neuronal dysfunction * History of smoking, alcoholism, and chronic drug intake. Baseline Parameters The baseline parameters of subjects recorded were blood pressure (BP) and heart rate (HR) which were taken as control or baseline values. First recorded within 30 s of standing up, then at the 1st, 2nd, 3rd, and 5th min.